Association of Caribbean States : prospects for a 'quantum leap' - Gill, Henry S. (North-South Centre Coral GablesUS, 1995)
Provides a review of the genesis, process, potential, objectives, and group dynamics of the Association of Caribbean States and analyzes the challenges faced by the organisation.